The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1002/1615-9861(200208)2:8<1026::aid-prot1026>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of human lysosomes: Application to monocytic and breast cancer cells

Abstract: To date, about fifty lysosomal hydrolases have been identified, and most of them are targeted towards the lysosomes through a specific mannose-6-phosphate (M-6-P) tag. As more lysosomal hydrolases were expected to be discovered, we performed a proteomic study of soluble lysosomal proteins. Human cells were induced to secrete M-6-P proteins which were affinity purified on immobilized M-6-P receptor. The purified proteins were resolved by two-dimensional electrophoresis and analyzed by mass spectrometry. Twenty-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0
4

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(67 citation statements)
references
References 46 publications
2
61
0
4
Order By: Relevance
“…A previous study identified 27 proteins from a soluble lysosomal fraction that bound to a mannose 6-phosphate affinity column (39). However, lysosomal membrane proteins are generally not transported to the organelle via this pathway as reflected by the highly sialylated state of their N-linked oligosaccharides.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study identified 27 proteins from a soluble lysosomal fraction that bound to a mannose 6-phosphate affinity column (39). However, lysosomal membrane proteins are generally not transported to the organelle via this pathway as reflected by the highly sialylated state of their N-linked oligosaccharides.…”
Section: Discussionmentioning
confidence: 99%
“…We wondered whether lysosome enzymes such as proteases might contribute to macrophage fusion, because they have been implicated in the formation of multinucleated myotubes (60,61). Therefore, we used a protease inhibitor mix, mostly non-cellpermeant, containing pepstatin A (inhibitor of aspartic proteases including cathepsin D), leupeptin (a broad inhibitor of cysteine proteases and cathepsin B), aprotinin (inhibitor of serine proteases), E64C (inhibitor of cysteine proteases such as cathepsins B, L, H, and K), and GM6001 (a broad metalloproteases inhibitor) (62)(63)(64). As shown in Fig.…”
Section: Formation Of Mgcs Is Dependent On Lysosomal Proteinsmentioning
confidence: 99%
“…To tackle this problem, either subcellular fractionation or enrichment strategies of "examine less to see more" or "divide and conquer" have been more widely adopted for proteomic studies besides orthogonal fractionation prior to MS analysis. Functional protein complexes or organelles (e.g., ribosome [11], spliceosome [12], phagosome [13], lysosome [14], exosome [15], vesicle coat [16], microsome [17], mitochondria [18], Golgi apparatus [19], nucleolus [20], etc.) have been selectively isolated and comprehensively analyzed.…”
Section: Introductionmentioning
confidence: 99%